Servqual dalam Kualitas Pelayanan terhadap Kepuasan Pasien Pengguna JKN di Puskesmas Karangrayung - Rahayu, Sri; Nasrawati (Universitas Ngudi Waluyo, 2024)
The harmony of sustainable and integrated services at community health centers is a quality in health services that can increase the level of public health. The quality of Puskesmas services appears to be not optimal because services are still received late. Patients’ perceptions of the quality of health services starting from the needs and expectations of the community appear to be lacking, so the quality of services provided by the Karangrayung Community Health Center needs to be researched. The service quality approach in service marketing research that was developed and popular is used as a reference in this research, namely identifying 5 components (servqual) in service quality. This research aims to determine the description of the 5 components of patient satisfaction in service quality services, namely reliability, responsiveness, assurance, empathy, tangibles for JKN users at the Karangrayung Community Health Center in 2023. With this type of quantitative descriptive research conducted from May to July 2023. Conclusion The sample using a purposive sampling technique was 100 respondents. Data analysis used Univariate analysis of variables, namely patient satisfaction with JKN users from 5 (five) dimensions. The results of research on JKN patient satisfaction from 5 dimensions, namely Reliability (reliability) 80 patients (80%), Responsiveness (responsiveness) 80 patients (80%), Assurance (guarantee) 83 patients (83%), Empathy (empathy) 75 patients (75%), Tangible (physical evidence) was 86 patients (86%). So it was concluded that the majority of respondents stated that health services at the Karangrayung Community Health Center for patients using JKN were satisfied and served well. ABSTRAK Keselarasan pelayanan yang berkesinambungan dan terintegrasi di puskesmas merupakan kualitas dalam pelayanan kesehatan yang dapat terjadi peningkatan pada derajat kesehatan terhadap kesehatan masyarakat. Layanan Puskesmas yang berkualitas terlihat belum maksimal dikarenakan masih didapatkan pelayanan yang terlambat. Persepsi pasien terhadap kualitas pelayanan kesehatan dimulai dari kebutuhan dan harapan masyarakat yang didapat terlihat kurang, sehingga mutu pelayanan yang telah diselenggarakan oleh Puskesmas Karangrayung perlu diteliti. Pendekatan kualitas pelayanan dalam riset pemasaran jasa yang dikembangkan dan popular dijadikan sebagai acuan dalam penelitian ini yaitu mengidentifikasi 5 komponen (servqual) dalam kualitas pelayanan. Penelitian ini bertujuan untuk mengetahui diskripsi dari 5 komponen kepuasan pasien dalam servquel kualitas pelayanan yaitu reliability, responsiveness, assurance, emphaty, tangibles pada pengguna JKN di Puskesmas Karangrayung tahun 2023. Dengan jenis penelitian deskriptif kuantitatif yang dilakukan pada bulan Mei sampai Juli tahun 2023. Pengambilan sampel dengan teknik purposive sampling sebanyak 100 responden. Analisis data yang digunakan analisi Univariat dari variabel yaitu kepuasan pasien pengguna JKN dari 5 (lima) dimensi. Hasil penelitian kepuasan pasien JKN dari 5 demensi yaitu Reliability (kehandalan) 80 pasien (80%), Responsiveness (daya tanggap) 80 pasien (80%), Assurance (jaminan) sebanyak 83 pasien (83%), Empathy (empati) sebanyak 75 pasien (75%), Tangible (bukti fisik) sebanyak 86 pasien (86%). Maka disimpulkan bahwa sebagian besar responden menyatakan bahwa pelayanan kesehatan di Puskesmas Karangrayung pada pasien pengguna JKN merasa puas dan dilayani dengan sudah baik.